(untitled) (Research, Society and Development, 2022)
ANVISA made changes to its regulations, setting new values for the fatigue tests, increasing the number of cycles that prostheses must endure without presenting failures. The standard used is ABNT NBR 7206-6:2013, in which all prostheses being commercialized must be tested in the new parameters. In this article, studies were conducted based on the requirement to revalidate the Co-26Cr-6Mo metallic alloy (ASTM F75). Microstructural characterizations (Optical and Scanning Electron Microscopies), and fatigue tests were carried out, with the aim of obtaining the mechanical behavior and features of the materials used in hip prostheses and comparing them with the standard. The grain size and inclusion contents were found to be controlled. Likewise, the prosthesis has withstand 10,000,000 cycles, and has not shown cracks, nor plastic deformations, enabling the biomedical use of this alloy according to the new regulations. Tensile test and liquid penetrant inspection were also carried out to take the parameters of the related physical properties. In the analysis with strain gauges, it was possible to detect the purely elastic deformation that occurred with the application of the load during fatigue tests, resulting in a slight variation of stress in the data acquisition system.